Buddhism and Marxism Through the Perspective of Bhimrao Ambedkar - Nam, Ong Van (Journal of Posthumanism, 2024)
This paper examines the ideologies of Buddha and Marx through the comparative lens of Bhimrao Ambedkar (1891-1956), whose work “Buddha or Marx” (1956) provides a socio-political analysis of their similarities and differences. Ambedkar’s analysis encompasses the historical conditions that shaped both thinkers, their philosophical starting points, approaches to human liberation, and visions for creating societies based on fairness and equality. As both a scholar deeply influenced by Buddhism and a political activist in India, Ambedkar offers a unique assessment of Marxism and its application through the “dictatorship of the proletariat” model. While comparative studies of Buddhism and Marxism are not novel, this examination gains particular significance in contemporary discourse as it illuminates how doctrines transform under societal pressures and how philosophical traditions from different cultural contexts can inform modern approaches to social justice, equality, and human rights.